2000
DOI: 10.1038/sj.bjp.0703718
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of L‐arginine uptake and protein tyrosine kinase activity for NO‐dependent vasorelaxation induced by stretch, isometric tension and cyclic AMP in rat pulmonary arteries

Abstract: 1 The NO-dependent component of cyclic AMP-induced vasorelaxation in rat pulmonary arteries is critically dependent on extracellular L-arginine but independent of endothelial cell intracellular [Ca 2+ ]. We examined whether L-arginine uptake was also essential for NO production induced by passive stretch or isometric tension, processes also reported to be Ca 2+ -independent. 2 The passive length-tension curve was depressed by physiological concentrations of L-arginine (400 mM; P50.05). Inhibition of the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
8
0
1
Order By: Relevance
“…It was not surprising that stimulation with PGF 2␣ alone resulted in increased production since the stimulation of NO production by contractile agonists is well documented (e.g., see Ref. 19) and indeed specifically with PGF 2␣ in IPA (16). However, the combination of SB-203580 and PGF 2␣ caused a rise in cGMP similar to that induced by PGF 2␣ alone, suggesting that under the conditions used in our experiments SB-203580 was not affecting the release of NO or its ability to stimulate guanylate cyclase.…”
Section: Discussionmentioning
confidence: 92%
“…It was not surprising that stimulation with PGF 2␣ alone resulted in increased production since the stimulation of NO production by contractile agonists is well documented (e.g., see Ref. 19) and indeed specifically with PGF 2␣ in IPA (16). However, the combination of SB-203580 and PGF 2␣ caused a rise in cGMP similar to that induced by PGF 2␣ alone, suggesting that under the conditions used in our experiments SB-203580 was not affecting the release of NO or its ability to stimulate guanylate cyclase.…”
Section: Discussionmentioning
confidence: 92%
“…Taken together, our data suggest that NO production evoked by leptin is realized through an intracellular calcium-independent signaling pathway converging on Akt phosphorylation, which does not involve the activation of PI 3-kinase but instead requires tyrosine phosphorylation that is sensitive to erbstatin A but not genistein. This latter finding, that two diverse tyrosine kinase inhibitors realize different effects, could seem conflicting, but several reports have described a similar lack of effect of genistein on NO production realized by application of other stimuli, suggesting that Akt phosphorylation and the consequent NO release is regulated by one or more tyrosine kinases with differential sensitivity to the inhibitors used (29,30). It is noteworthy to emphasize that the inhibitory effect of erbstatin A cannot be ascribed to a direct interference with eNOS tyrosine phosphorylation, because a preliminary event in the eNOS activation cascade, such as Akt phosphorylation, is also inhibited by erbstatin A.…”
Section: Discussionmentioning
confidence: 94%
“…In vessels, it has been demonstrated that L-arginine uptake is involved in NO production caused by mechanical stimuli, but L-arginine is not required for ACh-induced NO production [25, 26] or for the increase in eNOS activity by tyrosine phosphorylation [57]. Results from the present study demonstrate that at 2.5 g RT, the extracellular calcium concentration, NOS or tyrosine kinase inhibitors and L-arginine did not alter passive tension.…”
Section: Discussionmentioning
confidence: 99%